Rice Crop Disease Identification and Classifier - Lahu Bansod, Vishakha (International Journal of Computer Sciences and Engineering, 2025)
many papers have been referred, covering the work on rice plant diseases and other different plants and fruits, and present a survey of few papers based on important criteria. These criteria include size of image dataset, no. of classes (diseases), preprocessing, segmentation techniques, types of classifiers, accuracy of classifiers etc. Utilize this survey and study to propose a work on detection and classification of rice crop diseases